2022
DOI: 10.35440/hutfd.1185729
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Platelet and D-Dimer Levels in Predicting Prognosis in Intensive Care Patients Diagnosed With COVID-19

Abstract: Background: The pathophysiology of coagulopathy in patients with Corona virus disease 2019 (COVID-19) and its clinical manifestations remain unclear. However, several studies have reported abnormal coagulation parameters, notably in patients with COVID-19 associated pneumonia and acute respiratory distress syn-drome. Although the underlying mechanism of COVID-19 coagulopathy remains unknown, it has been sug-gested to be a form of disseminated intravascular coagulation. We aimed to determine the predictive valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…In our study, sensitivity and specificity of aPTT were 59.7% and 59.2%, respectively, whereas compared to the investigation conducted by Citu et al, 37 the specificity values were significantly lower in our study and differed in this respect. In another study, Altay et al 38 investigated the relationship between platelet and d-dimer levels and COVID-19 outcome and demonstrated that platelet levels did not constitute a significant difference according to survival groups ( P = .193). On the contrary, in our study, platelet levels were seen to be lower in the exitus group and constituted a significant difference ( P < .001).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, sensitivity and specificity of aPTT were 59.7% and 59.2%, respectively, whereas compared to the investigation conducted by Citu et al, 37 the specificity values were significantly lower in our study and differed in this respect. In another study, Altay et al 38 investigated the relationship between platelet and d-dimer levels and COVID-19 outcome and demonstrated that platelet levels did not constitute a significant difference according to survival groups ( P = .193). On the contrary, in our study, platelet levels were seen to be lower in the exitus group and constituted a significant difference ( P < .001).…”
Section: Discussionmentioning
confidence: 99%